2014
DOI: 10.1590/s0100-55022014000300004
|View full text |Cite
|
Sign up to set email alerts
|

Publicación de trabajo de conclusión de curso de estudiantes de medicina de una universidad peruana

Abstract: OBJETIVO: Describir las características y tiempo de publicación de los trabajos de investigación desarrollados para fines de obtención de grado por estudiantes de medicina humana de una universidad peruana. MÉTODOS: Se recolectó información de los trabajos de investigación para obtener el grado académico de bachiller en medicina de una universidad peruana sustentados durante los años 2006, 2007 y 2008. Dos autores realizaron una búsqueda sistemática de dichos trabajos en Pubmed, BVS y Google académico de acuer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…2,8 However, it has been reported that the frequency of publication of medical undergraduate theses in indexed journals in Peru is very low, ranging from 1% to 23.6%. [9][10][11][12][13][14][15][16][17] Likewise, Peruvian studies have identified barriers and limitations to the completion of theses by undergraduate medical students, which include administrative procedures, preparation and submission of the thesis, approval of the research protocol, request for the assignment of a thesis advisor, nomination of the thesis jury, 18,19 self-perceived lack of research knowledge, insufficient time or resources, 20 and unavailability of trained advisors. 21 However, there are no studies addressing the barriers and limitations perceived by new graduates regarding the publication of their theses, which is relevant both to understand the current context of medical programs and to implement measures aimed at encouraging the publication of undergraduate works in scientific journals.…”
Section: Introductionmentioning
confidence: 99%
“…2,8 However, it has been reported that the frequency of publication of medical undergraduate theses in indexed journals in Peru is very low, ranging from 1% to 23.6%. [9][10][11][12][13][14][15][16][17] Likewise, Peruvian studies have identified barriers and limitations to the completion of theses by undergraduate medical students, which include administrative procedures, preparation and submission of the thesis, approval of the research protocol, request for the assignment of a thesis advisor, nomination of the thesis jury, 18,19 self-perceived lack of research knowledge, insufficient time or resources, 20 and unavailability of trained advisors. 21 However, there are no studies addressing the barriers and limitations perceived by new graduates regarding the publication of their theses, which is relevant both to understand the current context of medical programs and to implement measures aimed at encouraging the publication of undergraduate works in scientific journals.…”
Section: Introductionmentioning
confidence: 99%
“…La producción de tesis de la UPSJB fue de tendencia baja (11.3%), e irregular similar a Osada J y col. 37 (2014), quienes reportaron una tendencia baja e irregular en la producción de tesis en el periodo 1998 -2008, variando entre menos de 5 y más de 10 sustentaciones de tesis por año, debido a otras opciones de titulación donde no pedían tesis para la titulación.…”
Section: Resultsunclassified